Advances in practical feed formulation and adoption for hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) aquaculture. (23rd July 2021) - Nankervis, Leo; Cobcroft, Jennifer M.; Nguyen, Nguyen V.; Rimmer, Michael A.
Abstract: Grouper aquaculture is currently trending towards production of hybrids, due to their improved growth and disease resistance. The predominant cross is between tiger grouper ( Epinephelus fuscoguttatus ) females and giant grouper ( Epinephelus lanceolatus ) males (TGGG). Sustainable TGGG aquaculture development is limited by reliance on wild‐caught 'trash' fish as feed rather than commercially formulated feeds. Specific TGGG nutrient requirement values remain limited, especially for larger fish that consume the highest volumes of feed. This limits the effectiveness of formulated feeds to provide optimal growth and feed conversion in an economically efficient manner. This review examines the current knowledge of hybrid grouper nutrient requirements for grow‐out feeds and identifies knowledge gaps to inform further research that will enable development of cost‐effective feeds that optimize fish growth, feed conversion and health. Current best practice in TGGG feeds specifies a relatively high protein requirement (53.5% crude protein), with higher arginine and lower lysine requirements than previously reported for grouper species. Like other groupers, the hybrid appears to require low lipid levels (10–14%); however, it remains to be elucidated whether this increases significantly with body size. The nutrient requirement data within this review provide a starting point for development of specific hybrid grouper feeds. However, commercialization of such feeds requires better understanding of the socio‐economic context of the target industry. While formulated feeds may be more cost‐effective, their implementation is limited by inferior growth compared with 'trash' fish. Performance gains are expected through increased understanding of size‐specific nutrient requirements and specific raw material quality criteria.